Law and regulation of public offering of corporate securities - Singh, Raghvendra K.; Singh, Shailendera K. (New Delhi : Oxford University Press, 2016)
This title examines the legal framework affecting the concept of public offerings of securities in India. It also deals with the liability of the players involved, as well as protection available to the investors. The overarching goal is to provide a comprehensive legal exposition of public offering of securities in the backdrop of corporate finance and securities laws.
This edition previously issued in print: 2016.
Includes index.
Specialized.
Description based on online resource; title from home page (viewed on September 22, 2016).
Keywords: Going public (Securities) -- Law and legislation -- India; Law; Laws of specific jurisdictions & specific areas of law